PENERAPAN LAYANAN KONSELING KELOMPOK DENGAN TEKNIK TOKEN ECONOMY UNTUK MENINGKATKAN KEDISIPLINAN PESERTA DIDIK KELAS X KK DI SMK NEGERI 4 PALANGKA RAYA - Sinta; Romiaty; Nopi Feronika (STKIP Subang, 2026)
Discipline is about students' ability to control themselves according to established and agreed-upon rules. These rules include punctual attendance, completing assignments on time, working independently, behaving according to norms, and adhering to agreed-upon rules. Discipline is an appropriate method for building students' character, but it is not too harsh in changing their behavior. This study aims to explore the use of group counseling services using the technique.token economy as a step to improve student discipline. In this study, the technique token economyused as a solution to address low student discipline. This technique encourages students to behave positively, learn self-control, and understand the concept of rewards. This study used a designpre-experimental with the method One-Group Pre-test-Post-test Design. Samples were taken using the techniquepurposive sampling The research subjects were 5 students of class X KK at SMK Negeri 4 Palangka Raya. The author distributed questionnaires to measure the improvement of student discipline. The data were analyzed using the t-test.Paired Sample T-testwith the help of the SPSS version 25 application. The results of the study show that the t-test calculation using the testpaired sampel t test produces a sig. value of 0.01 < 0.05 and the comparison of the calculated and ttable values ​​is 8.856 > 2.131. It can be concluded that after providing services using the technique tocen economythere is a significant increase in discipline. This means that the null hypothesis (H0) which states “Group counseling services use group counseling techniques token economy Unable to improve the discipline of class X KK students at SMK Negeri 4 Palangka Raya in the 2024/2025” academic year rejected and the alternative hypothesis (Ha) which states “Group counseling services use group counseling techni ques token economycan improve the discipline of class X KK students at SMK Negeri 4 Palangka Raya in the 2024/2025 academic year” accepted.